2012
DOI: 10.1093/hmg/dds408
|View full text |Cite
|
Sign up to set email alerts
|

The ciliopathy disease protein NPHP9 promotes nuclear delivery and activation of the oncogenic transcriptional regulator TAZ

Abstract: Nephronophthisis (NPH) is a genetically heterogenous kidney disease and represents the most common genetic cause for end-stage renal disease in children. It is caused by the mutation of genes encoding for the nephrocystin proteins (NPHPs) which localize to primary cilia or centrosomes, classifying this disease as a 'ciliopathy'. Recently, it has been shown that NPHP4 acts as a potent negative regulator of mammalian Hippo signalling by interacting with the Lats protein kinase and controlling the phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 35 publications
0
58
0
Order By: Relevance
“…Members of the nephrocystin (NPHP) family, established primary cilia-associated proteins [159], induce TAZ (and YAP) activity. NPHP4 binds to LATS and negatively regulates LATS activity, whereas NPHP3 and NPHP9 bind directly to TAZ and potentially compete with 14-3-3 binding to relieve cytoplasmic retention [160,161]. Therefore, members of the NPHP family increase transcriptional activity of YAP and TAZ [153].…”
Section: Yap/taz As a Signaling Networkmentioning
confidence: 99%
“…Members of the nephrocystin (NPHP) family, established primary cilia-associated proteins [159], induce TAZ (and YAP) activity. NPHP4 binds to LATS and negatively regulates LATS activity, whereas NPHP3 and NPHP9 bind directly to TAZ and potentially compete with 14-3-3 binding to relieve cytoplasmic retention [160,161]. Therefore, members of the NPHP family increase transcriptional activity of YAP and TAZ [153].…”
Section: Yap/taz As a Signaling Networkmentioning
confidence: 99%
“…For example, NPHP4 (nephrocystin-2: OMIM 607215) interacts with and inhibits the LATS1 kinase, leading to the nuclear accumulation of the transcriptional co-activators YAP and TAZ, two proteins involved in the HIPPO (hypoxia) signaling system [33]. NPHP9 (also known as NEK8–OMIM 609799) has been found to interact with TAZ, leading to the nuclear localization of the NPHP9–TAXZ complex [34]. TAZ is normally exported to the cytoplasm through interactions with 14-3-3 proteins; NPHP9 appears to compete with 14-3-3 proteins for TAZ binding.…”
Section: Examples Of Cilia-associated Proteins With Known Nuclear Rolesmentioning
confidence: 99%
“…Recent studies have shown that the ciliopathy proteins NPHP4 and NPHP9 negatively regulate the Hippo pathway and promote nuclear targeting of TAZ 22,23 . In addition, the Hippo pathway component MST1/2-SAV complex was identified as a regulator of a cilium disassembly pathway involving AURKA and HDAC6 (ref.…”
mentioning
confidence: 99%